Sexual Intercourse with a Corpse as a Crime Against Society and the Urgency of Its Regulation in the New Penal Code - Erdianto Effendi; Rena Yulia; Heni Susanti (Universitas Muhammadiyah Purwokerto, 2024)
Murder in criminal law has been regulated in detail, but the actions after murder have not been regulated in such a way. So that the perpetrator is only charged with murder when there are other actions that have different elements. For example, mutilation, intercourse with corpses, and even eating corpses. This paper will examine the acts committed against a corpse after murder, namely intercourse with a corpse. The study is conducted on articles in the New Criminal Code. The purpose of this study is to find out how the New Criminal Code regulates the act of intercourse committed against a corpse after being killed as a response to the development of human actions today. The research method used is normative legal research with a case approach. The result of this research is known that the New Criminal Code does not regulate intercourse with corpses, but only regulates interference with funerals and corpses. This article focuses more on the corpse that has been buried and the destruction of the grave. Regulations regarding corpses that are molested, sodomized or mutilated and eaten after being killed have not been regulated. In fact, these acts currently occur frequently. The act of copulation with a corpse is committed after the victim is killed and before the victim is buried. These acts can be different from the interference with funerals and corpses as referred to in the New Penal Code.